2020
DOI: 10.7759/cureus.8030
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the United States Preventative Services Task Force Screening Guidelines for Breast Cancer in a Hispanic Underserved Population

Abstract: There are several major breast cancer guidelines that have been promoted by various health organizations. Arrowhead Regional Medical Center (ARMC) Family Health Centers adopted the current guideline by the U.S. Preventive Services Task Force (USPSTF), which recommends breast cancer screening with mammograms starting at age 50 for low-risk women. This study evaluates the effectiveness of this screening guideline in the selected Hispanic underserved population in San Bernardino, California (CA). This is a retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The Centers for Disease Control and Prevention report that Caucasians have the highest incidence of breast cancer in the U.S. A previous study conducted at ARMC suggested that Hispanics had the highest incidence of breast cancer in San Bernardino County, correlating with the racial demographics of the county [21]. There are conflicting viewpoints on the importance of race and ethnicity in breast cancer diagnosis and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The Centers for Disease Control and Prevention report that Caucasians have the highest incidence of breast cancer in the U.S. A previous study conducted at ARMC suggested that Hispanics had the highest incidence of breast cancer in San Bernardino County, correlating with the racial demographics of the county [21]. There are conflicting viewpoints on the importance of race and ethnicity in breast cancer diagnosis and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The lower observed utilization of mammograms among women with SPD and MPD also warrants further investigation to determine how best to improve mammogram use for these individuals. To address the general problem of underutilization of preventative services [32,33] and the specific issue of breast cancer screening, [7][8][9] policymakers and healthcare providers must pay close attention to women with both MPD and SPD. Due to the simplicity of its administration, practitioners can utilize the Kessler-6 scale as a screener to identify women (MPD and SPD) at risk of not adhering to the USPSTF recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Moreover, there are reports of disparities in screening rates among the medically underserved population. [8] In particular, disparities in screening related to mental illness remain among the least studied among the disparities. [9] Results from the studies that have examined cancer screening in women with psychological distress have been mixed.…”
Section: Introductionmentioning
confidence: 99%